2022
DOI: 10.3390/app12115466
|View full text |Cite
|
Sign up to set email alerts
|

An Effect of Radiation and MHD Newtonian Fluid over a Stretching/Shrinking Sheet with CNTs and Mass Transpiration

Abstract: The invention of carbon nanotubes (CNT) has a wide range of industrial and medical applications. The notion of boundary layer flow is used in medicine, particularly in nanomedicine, and the use of magnetic fields is used to treat cancer tumour growth. The governing PDEs are altered into ODEs with the help of suitable transformations. The mass transfer of a chemically reactive species and the flow of MHD over a stretching plate subjected to an inclined magnetic field are investigated, and analytical solutions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The new transformed equations are, ℎ 𝑛 (𝛿𝑙 𝑛 + 𝛿𝑙 𝑛−1 ) = (𝑟 5 ) 𝑛 (39) The equations are given below in their condensed form, once more utilizing equations (35)(36)(37)(38)(39) in equations (30)(31)(32)(33); Recalling the precise boundary conditions without iteration, we take steps to make sure that these correct values are preserved across all iterations.…”
Section: Computational Scheme and Solution Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The new transformed equations are, ℎ 𝑛 (𝛿𝑙 𝑛 + 𝛿𝑙 𝑛−1 ) = (𝑟 5 ) 𝑛 (39) The equations are given below in their condensed form, once more utilizing equations (35)(36)(37)(38)(39) in equations (30)(31)(32)(33); Recalling the precise boundary conditions without iteration, we take steps to make sure that these correct values are preserved across all iterations.…”
Section: Computational Scheme and Solution Methodologymentioning
confidence: 99%
“…They found that the temperature is enhanced with higher Prandtl number and the volumetric percentage of micro particles. The viscous dissipative, magnetohydrodynamics and radiations impacts on laminar fluid analysis along the stretching surface were examined by Maranna et al [35]. For various engineering applications, Mabood et al [36] carried out magnetohydrodynamics and entropy analysis for Jeffrey-nanofluid phenomenon across the stretching surface.…”
Section: Introductionmentioning
confidence: 99%
“…By using Rosseland's diffusion approximation for radiation and following [40–44], the radiative flux qr${q}_r$ is of the form qrbadbreak=4σ3κT4y,$$\begin{equation} {q}_r = - \frac{{4{\sigma }^*}}{{3{\kappa }^*}}\frac{{\partial {T}^4}}{{\partial y}}, \end{equation}$$where σ${\sigma }^*$ and κ${\kappa }^*$ are the Stefan‐Boltzmann constant and the mean absorption coefficient. It is assumed that temperature differences within the flow are small enough to express fourth‐power term in radiative flux as a linear function of temperature.…”
Section: Mathematical Formulation and Derivationmentioning
confidence: 99%
“…By using Rosseland's diffusion approximation for radiation and following [40][41][42][43][44], the radiative flux 𝑞 𝑟 is of the form…”
Section: Mathematical Formulation and Derivationmentioning
confidence: 99%
“…Abulnaja et al [30] performed unsteady free/forced convection flow filled with nanofluid across the straight disc placed in a porous material in the presence of variable surface temperature. Maranna et al [31] analyzed the mass transpiration phenomena with MHD and radiation effects on viscous fluid past a stretched shape. Mabood et al [32] performed Jeffrey nanofluid phenomena with entropy and MHD effects along the stretched geometry for various engineering application.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%